2011
DOI: 10.1016/j.ejcts.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Alternative paratracheal lymph node dissection in left-sided hilar lung cancer patients: comparing the number of lymph nodes dissected to the number of lymph nodes dissected in right-sided mediastinal dissections

Abstract: Lymphadenectomy of the paratracheal area via left thoracotomy without ductus arteriosus division and mobilization of the aortic arch is technically feasible. From these data, regardless of approach, more lymph nodes are obtained from the right paratracheal space; this appears to be due to the fact that there are more right-sided paratracheal lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This study showed that a median of 12 nodes in the right and 11 nodes in the left chest have been resected from the mediastinum in healthy subjects; however, literature concerning mediastinal nodal dissection reveals discrepancy, creating a real confusion for chest surgeons. Excised number of mediastinal nodes with SND have been presented to be 17.3 nodes [3], 38.9 nodes (bilateral mediastinal dissection with transcervical technique, excluding station 9) [8], 40.3 in the right vs. 37.1 in the left (including hilar resion and stations 11 and 12) [9], 8.6 nodes (with video assisted mediastinoscopic lymphadenectomy (VAMLA) from paratracheal stations and station 7 [10], 16 nodes with VAMLA [11], and 8.4 nodes from paratracheal region only via left thoracotomy [12]. The presence of either micro metastasis, reaction to a tumor or to an infection in the lung distal to the tumor may be the reason for these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that a median of 12 nodes in the right and 11 nodes in the left chest have been resected from the mediastinum in healthy subjects; however, literature concerning mediastinal nodal dissection reveals discrepancy, creating a real confusion for chest surgeons. Excised number of mediastinal nodes with SND have been presented to be 17.3 nodes [3], 38.9 nodes (bilateral mediastinal dissection with transcervical technique, excluding station 9) [8], 40.3 in the right vs. 37.1 in the left (including hilar resion and stations 11 and 12) [9], 8.6 nodes (with video assisted mediastinoscopic lymphadenectomy (VAMLA) from paratracheal stations and station 7 [10], 16 nodes with VAMLA [11], and 8.4 nodes from paratracheal region only via left thoracotomy [12]. The presence of either micro metastasis, reaction to a tumor or to an infection in the lung distal to the tumor may be the reason for these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node counting was done as previously described. 16) Fissures were divided by staplers or coagulation in all resections. Basically, for a segmentectomy operation level 11 and 12 nodes were dissected completely and sent for frozen section analysis.…”
Section: Surgical Techniquementioning
confidence: 99%
“…For a right-sided NSCLC, paratracheal lymph nodes can be removed completely (Figure 1, Video 1). For left sided tumors, complete resection of paratracheal nodes may pose to be more challenging, but has been performed by several authors, including one of the authors of this manuscript (Figure 2, Video 2) (25). Bilateral paratracheal lymph node dissection has also been performed and presented for right and left sided tumors.…”
Section: Extent Of Lymph Node Dissectionmentioning
confidence: 99%